2012
DOI: 10.1038/nature10804
|View full text |Cite|
|
Sign up to set email alerts
|

Functional dissection of lysine deacetylases reveals that HDAC1 and p300 regulate AMPK

Abstract: First identified as histone-modifying proteins, lysine acetyltranferases (KATs) and deacetylases (KDACs) antagonize each other through modification of the side chains of lysine residues in histone proteins1. (De)acetylation of many non-histone proteins involved in chromatin, metabolism or cytoskeleton regulation were further identified in eukaryotic organisms2–6, but the corresponding modifying enzymes and substrate-specific functions of the modification are unclear. Moreover, mechanisms underlying functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 38 publications
1
73
1
Order By: Relevance
“…Since VPA is a known inhibitor of HDAC1 (Phiel et al, 2001), which has been previously shown to regulate AMPK phosphorylation/activation (Lin et al, 2012), our data demonstrating that treatment with VPA resulted in increased levels of phosphorylated AMPK were potentially in conflict with this finding. We found that although inhibition of deacetylase activity was observed following treatment of mouse nuclear extracts and human recombinant HDAC1with VPA, the acetylation of AMPK in primary mouse hepatocytes was unchanged following treatment with VPA as compared with vehicle treatment, indicating that any inhibition of HDAC1 activity that may have occurred as a result of VPA treatment did not impact the acetylation status of AMPK as compared with vehicle-treated control samples.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Since VPA is a known inhibitor of HDAC1 (Phiel et al, 2001), which has been previously shown to regulate AMPK phosphorylation/activation (Lin et al, 2012), our data demonstrating that treatment with VPA resulted in increased levels of phosphorylated AMPK were potentially in conflict with this finding. We found that although inhibition of deacetylase activity was observed following treatment of mouse nuclear extracts and human recombinant HDAC1with VPA, the acetylation of AMPK in primary mouse hepatocytes was unchanged following treatment with VPA as compared with vehicle treatment, indicating that any inhibition of HDAC1 activity that may have occurred as a result of VPA treatment did not impact the acetylation status of AMPK as compared with vehicle-treated control samples.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been previously demonstrated in yeast and HepG2 cells (a hepatocarcinoma cell line) that the activity of AMPK is regulated by HDAC1 (Lin et al, 2012). Deacetylation of AMPK by HDAC1 was shown to facilitate its interaction with upstream kinases, thereby stimulating the phosphorylation and activation of AMPK.…”
Section: Vpa Stimulates Phosphorylation Of Ampk and Acc In Hepatocytesmentioning
confidence: 99%
“…13 AMPK may modify transcription via phosphorylation of a large and growing number of transcription factors and chromatin proteins. 12,[14][15][16][17][18][19][20] Critically, these include ATF1. 8 Purified AMPK phosphorylated recombinant purified ATF1 in an in vitro kinase assay in a cell-free system, in an article defining AMPK-mediated phosphorylation of CREB-family proteins in vivo in skeletal muscle during exercise.…”
Section: ′-Amp-activated Protein Kinase (Ampk)mentioning
confidence: 99%
“…In acute myelogenous leukemia, inhibition of mTOR signaling has been proposed to overcome HDAC inhibitor resistance (64) and, conversely in DLBCL cells, inhibition of HDACs to rescue mTOR inhibitor resistance (55). Even more recently, HDAC1 has been directly shown to regulate metabolism in mammalian cells through deacetylation of the AMPK kinase, thus leading to its interaction and activation by the upstream LKB1 kinase (65). In this way, HDAC1 can act as a direct energy sensor in the cells, hinting at complex regulatory links among metabolism, DDR, and autophagy.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%